Perlindungan Hukum Terhadap Kekerasan Seksual Pada Anak Menurut Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak - Absi, Warmiyana Zairi; Novianti, Sella; Pertiwi, Bella (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Sexual violence is a pressing legal issue because it concerns the human rights of victims and causes serious physical and psychological damage. In Indonesia, cases of sexual violence against children continue to rise, yet many victims still choose to remain silent and do not report the incidents to law enforcement authorities or child protection agencies. This reality has prompted research to examine the extent of the implementation and effectiveness of legal protection for child victims of sexual violence in Palembang City based on Law No. 35 of 2014 on Child Protection. The research was conducted using a qualitative method through a legal-empirical approach, combining literature review and direct interviews with relevant parties. The research findings are expected to provide an overview of legal protection practices while identifying the factors that contribute to the occurrence of sexual violence against children.